An investigation into the importance and measurement of flexibility as perceived in South African manufacturing - Van der Merwe, Carel J.(Carel Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing) -- University of Stellenbosch, 1998.